Educational Financing Management: Concepts, Implications and Quality Development - Arenibi Maruhawa (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
Education financing is part of implementing quality education in educational institutions or academic units that program their institutions to become quality institutions. However, the tug-of-war of interest in providing funding is often experienced by educational institutions so that educational institutions stand idly by, waiting for donors to obtain funding to create quality educational institutions. This research is a type of library research, namely research that is carried out through critical and in-depth studies of library materials that are considered relevant. Find in the field. The research findings indicate that the cost of education has an important influence on improving the quality of education. The use of education costs evenly is expected to improve the overall quality of education in all circles of society. Furthermore, cooperation between the government, local government, and the community needs to support a qualified and high-quality learning process. The high cost of education will follow the qualified and high-quality education. The higher the quality of education, the higher the cost of education, and the lower the quality of education, the lower the cost of education